PERAN ORANG TUA DALAM PEMBINAAN AKHLAK ANAK MELALUI MEDIA INTERNET - Cucu Komariah; Sanusi Uwes; Manpan Drajat; Imam Tabroni (FAKULTAS TARBIYAH IAI SULTAN MUHAMMAD SYAFIUDDIN SAMBAS, 2021)
The research method used is descriptive with a qualitative approach. Through interviews, observation and documentation study, data comes from interview manuscripts, field notes, photos, video tapes, personal documents, notes or memos, and other official documents. The research objective was to analyze and find out the role of parents in developing children's morals through the internet media (Mobile) during the covid-19 period. Respondents were 10 families with SMP/MTs children in Babakan Cikao Purwakarta, West Java. The results obtained by children live with their grandparents because their parents work as female workers abroad. F Of the ten families, one family whose parents have the ability to operate internet media (handphont), nine families of technology failures (Gatek). The research finding shows that moral development through the internet media (handphont) is carried out through habituation and giving direct examples from parents.